2023
DOI: 10.58256/rjah.v4i2.1195
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the metafunctions to improve EFL learners’ writing ability in the perspective of systemic functional linguistics

Herman Herman,
Muhammad Rafiek,
Titik Agustina
et al.

Abstract: Writing in academic English is challenging and complex to learn, the root reasons for the issue, may include differences in the cultural backgrounds of the students, a deficiency in critical thinking skills, and a deficiency in linguistic proficiency. This study set out to investigate how metafunctions may be used to enhance students' writing skills. A research approach incorporating a qualitative case study will be employed to assess ninth-grade students' text composition. The data were gathered through colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Qualitative research is a research process that aims to understand human or social phenomena by constructing a complete and complex picture that can be expressed in words, presenting informants' views in detail, and carried out in appropriate conditions (Walidin, Saifullah & Tabrani, 2015;Andayani et al, 2023). Sugiyono (2012: 13) states that descriptive research is conducted to determine the value of an independent variable, one or more variables (free), without making comparisons or relationships with other variables (Hulu et al, 2023;Herman et al, 2023).…”
Section: Methodsmentioning
confidence: 99%
“…Qualitative research is a research process that aims to understand human or social phenomena by constructing a complete and complex picture that can be expressed in words, presenting informants' views in detail, and carried out in appropriate conditions (Walidin, Saifullah & Tabrani, 2015;Andayani et al, 2023). Sugiyono (2012: 13) states that descriptive research is conducted to determine the value of an independent variable, one or more variables (free), without making comparisons or relationships with other variables (Hulu et al, 2023;Herman et al, 2023).…”
Section: Methodsmentioning
confidence: 99%
“…Halliday in Herman, et al [3] found that the development of language competence is the ability to master three basic language functions which he called "meta-functions" of which the "ideational function" expresses content helps determine the speaker's way of seeing things, "interpersonal function" establishes and maintains relationships, defines social groups, identifies and strengthens personal characteristics and the "textual function" helps create a link between the language itself and the characteristics of the situation in which it is used, helping the speaker (or writer) construct paragraphs of discourse appropriate to the situation and at the same time assume that any linguistic unit is the actualization of the above three functions [4].…”
Section: Theory Of Language Abilitymentioning
confidence: 98%
“…Moreover, teaching writing skills in Indonesia, especially at the college level, requires enormous effort. Teaching writing does not only focus on the grammatical accuracy or the connection between sentences or paragraphs, but also there are some components and competencies that should be considered, i.e., social function, language and semantic features of the text, logical development of ideas, organization, cohesion and coherence, punctuation, style, expression quality, spelling, and meaning (Graham, 2019;Herman et al, 2023;Leli, 2020;Syam, 2020). However, instead of paying attention to developing writing skills, most teachers in English as a foreign language classroom are primarily concerned with teaching writing conventionally, which they emphasize reinforcing grammatical accuracy (Afzal et al, 2022).…”
Section: Introductionmentioning
confidence: 99%